Monitoring The Patient’s Blood Pressure Based on The Internet of Things (loT) - Alya khalid abdullatif abdullah; Akram Ali Yousif AL-Mohammed; Mayar jawad Kadhim; Mohammed Mahdi Hassan Hadi; Ahmed nail adil (American Journal of Biodiversity, 2025)
The Internet of Things (IoT) has revolutionized the healthcare industry by enabling remote monitoring and management of patient’s health conditions. One such application of IoT is in monitoring patients’ blood pressure, which is crucial for managing hypertension and other related conditions. This paper provides an abstract of the implementation of an IoT-based system for monitoring patients’ blood pressure. The system consists of a blood pressure sensor, a microcontroller, and a wireless communication module. The sensor measures the patient’s blood pressure, and the microcontroller processes the data and sends it wirelessly to a central monitoring station. The monitoring station receives the data and analyzes it to detect any anomalies or changes in the patient’s blood pressure. The system can provide real-time monitoring, alerting medical professionals to any changes in the patient’s blood pressure, and enabling timely intervention and treatment. The use of IoT in blood pressure monitoring has the potential to improve patient outcomes, reduce healthcare costs, and increase patient satisfaction.